The Challenge of Urban and Regional Development in the Future - Tedjo Suminto (Forum Geografi, 1995)
The task of development is part of the overall national task carried out along governance. This task has been entrusted to the government as a gradual long-term task, planning, and sustainable. Implied in it, the intention to achieve a better state. Contained within the dimension of time setting goals, achieving goals, and overall utilization of benefits for citizens throughout the country. Enshrined also be aware that there will be found a variety of difficulties, limitations, and problems that must be solved. The problems of urban development in Indonesia can be viewed from two approaches, namely macro and micro approaches. A macro approach urban problems are reviewed in the context of the region (national scale). While the approach is seen as a micro city neighborhoods. This problem is closely related to the natural growth of the city population and population migration. Based on research on urban and regional development, it can be concluded: 1) the problem of urbanization of rural and small towns to large cities should be addressed; 2) urban spatial arrangements should be improved to do with increasingly limited land for development and urban development; 3) the provision of facilities and infrastructure of the city, city management, and financing of urban development, integration between government, society, and the private sector should be increased; 4) study of urban models that can accommodate all the problems of the city should be developed continuously.